2007
DOI: 10.1111/j.1365-2982.2007.00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Recto‐colonic reflex is impaired in patients with irritable bowel syndrome

Abstract: Background: Motor and sensory dysfunction of the gut are present in a subset of patients with irritable bowel syndrome (IBS). Recent studies have demonstrated the presence of a recto-colonic inhibitory reflex in healthy humans. It is not known whether this reflex exists in IBS. Methods: We studied rectal compliance, perception and the recto-colonic reflex by measuring volume responses of the descending colon to rectal distentions by barostat in 26 IBS patients and 13 healthy controls under both fasting and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 24 publications
1
13
0
2
Order By: Relevance
“…This was consistent with early studies of the rectosigmoid reflex by Connell et al (6), which showed an increase in motor activity in some SCI patients and healthy subjects. Using a variety of different protocols and techniques, others have shown a more definite reflex (14,28). The origin of this variability remains unclear, and the ideal distension-and-recording protocol for this reflex is yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with early studies of the rectosigmoid reflex by Connell et al (6), which showed an increase in motor activity in some SCI patients and healthy subjects. Using a variety of different protocols and techniques, others have shown a more definite reflex (14,28). The origin of this variability remains unclear, and the ideal distension-and-recording protocol for this reflex is yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…MDP has been used in a large number of studies to correct for differences in intra-abdominal pressure between subjects [4, 5, 10, 13, 14, 19, 20]. The variation that exists between the methods to determine MDP hampers the comparison between various studies.…”
Section: Discussionmentioning
confidence: 99%
“…Since this response is preserved even after a gastrectomy, the term "colonic motor response to eating" is preferable to "gastrocolonic reflex." 458 This reflex may contribute to the postprandial urge to defecate and to postprandial abdominal discomfort in IBS. A biphasic response with early (first 60 minutes) and late (120 and 150 minutes) components have also been described.…”
Section: Colonic Contractile Response To a Mealmentioning
confidence: 99%